Hard Fun: Further Discussions on an Undergraduate Project to (Re)Construct and Fire a Medieval Tile Kiln - Gaynor Wood (EXARC Journal)
This experiment, undertaken over a 12-month period in 2015 at Norton Priory Museum in Cheshire, formed part of a pedagogic case study and an experimental archaeology project. Here eight Archaeology and 12 Ceramics students from the University of Central Lancashire (UCLAN) researched, built, and fired a tile kiln using evidence from previous experimental archaeology projects on the site and other firing projects. The students undertook this activity because of their own interest in wood-firing kiln technology and in experimental archaeology. The kiln was fired as a public exhibition, and approximately one hundred hand-decorated tiles were fired on the site (Wood, 2013, 2021).